The Effects of Noxious Electrical Stimulation and Eccentric Exercise on Mechanical and Thermal Pain Sensitivity in Recreational Runners with Achilles Tendinopathy - Scott K. Stackhouse; Brian J. Eckenrode; Kathleen C. Madara (International Journal of Sports Physical Therapy)
# Background